Evaluation of Selected Drinking Water Quality Parameters Using CCME-WQI in Nakuru Municipality, Kenya - Keli , Margaret Mwikali; Munyao , Thomas Mutuku; Kipkorir, Emmanuel C. (Natural Science Journal, 2021)
Purpose: Reliable baseline information on overall quality status of drinking water at spatial and temporal scales is important in drinking water management systems, ensuring access to clean and safe drinking water. The study aimed at determining the suitability of natural and treated water for drinking in Nakuru Municipality, Kenya. An attempt was also made to explore the applicability of CCME-WQI (Canadian Council of Ministers of the Environment Water Quality Index) in evaluation of groundwater quality data for drinking uses. Methodology: The study adopted a stratified random sampling technique that was employed systematically in conjunction with point and line techniques to create stratas/sampling components while ensuring each water cluster was represented through the sampling process. Analytical values of electrical conductivity, pH, selenium, cadmium, chloride and fluoride were used to determine quality status of water sourced from river and boreholes and as input parameters in calculation of index values. The evaluation and characterization of natural borehole water quality for drinking purposes was made using the water quality index (WQI) of the Canadian Council of Ministries of the Environment (CCME). Results: The quality of natural and treated drinking water was found to be fresh in pH, chloride and electrical conductivity but contaminated in selenium, cadmium and fluoride in line with respective regulatory standards for drinking water. Based on the CCME-WQI, index values for all sampled sites representing natural borehole water were calculated in a range of 29.83 to 37.71 with an average value of 31.05 and ranked as poor. Unique contribution to theory, practice and policy: Considering the limitations associated with the conventional methods in water quality monitoring, there is need to utilize other scientific based methods that can fill in the gaps to improve the current state of governance and practice of drinking water management systems. The CCME-WQI method as applied in this study can be utilized in evaluation of water quality monitoring data to facilitate water resources operational management and their allocation for different uses.